Disentangling the Link between Diverse Social Networks and Creativity: The Role of Personality Traits. (28th April 2023) - Soler-Pastor, Elia; Bobowik, Magdalena; Benet-Martínez, Verónica; Repke, Lydia
Abstract: Past studies have shown that being exposed to ethnocultural diversity can positively impact individual creativity. Yet, little is known about the interplay between situational (i.e., diversity) and dispositional (e.g., personality) factors in predicting creativity. Taking a person-situation approach, we use social network data to test the moderating role of personality in the relationship between having an ethnoculturally diverse network and creativity. Moreover, we investigate these questions in a diverse community sample of immigrants residing in the city of Barcelona ( N = 122). Moderation analyses revealed that network diversity predicted higher levels of creativity in migrant individuals with medium to high levels of extraversion, and in those with low to medium levels of emotional stability. These results highlight the need to acknowledge the important role played by interacting individual-level dispositions and more objective meso-level contextual conditions in explaining one's ability to think creatively, especially in samples that have traditionally been underrepresented in previous literature.